Intervención optométrica en paciente masculino de 39 años edad con miopía moderada. - Diaz Contreras, Jorge Jacinto (2024)
Refractive problems are one of the leading causes of blindness worldwide. The detection of these visual conditions is of utmost importance, if they are not diagnosed in the early stages, they can develop the appearance of pathologies, such as glaucoma, retinal detachment, keratoconus, among others. The current study cites the clinical case of a 39-year-old male patient with moderate myopia. You experience the following clinical picture: Headache, Blurred vision, Eye tension and pain, Visual fatigue, Eye squinting. Characteristic symptoms of myopia. After the optometric review and the analysis of the information obtained in the patient's clinical history, according to the results of the measurement of visual acuity without correction, the patient binocularly reaches a visual acuity of 20/70, however after the application The subjective refraction technique achieves visual acuity of 20/20 with correction. The optometric tests applied gave a definitive diagnosis of Moderate Myopia. Taking into consideration the work activity, your habits and needs, the treatment to be used is single vision lenses with updated measurements and photochromic protection plus blue block and Anti-reflective. Additionally, the patient is scheduled to return for an optometric consultation after 15 days, he returns and indicates comfort and visual quality. Taking care of visual health is essential due to the direct relationship with human health and quality of life. The present clinical study highlights the importance of primary care in visual health.